Biofabrication of nanoparticles: sources, synthesis, and biomedical applications - Kulkarni, Deepak; Sherkar, Rushikesh; Shirsathe, Chaitali; Sonwane, Rushikesh; Varpe, Nikita; Shelke, Santosh; More, Mahesh P.; Pardeshi, Sagar R.; Dhaneshwar, Gargee; Junnuthula, Vijayabhaskarreddy; Dyawanapelly, Sathish (Frontiers in Bioengineering and Biotechnology, 2023)
Nanotechnology is an emerging applied science delivering crucial human interventions. Biogenic nanoparticles produced from natural sources have received attraction in recent times due to their positive attributes in both health and the environment. It is possible to produce nanoparticles using various microorganisms, plants, and marine sources. The bioreduction mechanism is generally employed for intra/extracellular synthesis of biogenic nanoparticles. Various biogenic sources have tremendous bioreduction potential, and capping agents impart stability. The obtained nanoparticles are typically characterized by conventional physical and chemical analysis techniques. Various process parameters, such as sources, ions, and temperature incubation periods, affect the production process. Unit operations such as filtration, purification, and drying play a role in the scale-up setup. Biogenic nanoparticles have extensive biomedical and healthcare applications. In this review, we summarized various sources, synthetic processes, and biomedical applications of metal nanoparticles produced by biogenic synthesis. We highlighted some of the patented inventions and their applications. The applications range from drug delivery to biosensing in various therapeutics and diagnostics. Although biogenic nanoparticles appear to be superior to their counterparts, the molecular mechanism degradation pathways, kinetics, and biodistribution are often missing in the published literature, and scientists should focus more on these aspects to move them from the bench side to clinics.